Sustaining Continuous Engagement in Value Co-creation Among Individuals in Universities Using Online Platforms: Role of Knowledge Self-Efficacy, Commitment and Perceived Benefits - Al-kumaim, Nabil Hasan; Alhazmi, Abdulsalam K.; Ramayah, T.; Shabbir, Muhammad Salman; Gazem, Nadhmi A. (Frontiers in Psychology, 2021)
Value co-creation (VCC) plays a major role in engaging knowledgeable individuals in a community through innovation, problem solving, and new service/product development. This study investigates the personal factors that influence individuals’ engagement in value co-creation in Higher Education Institutions (HEIs) through the use of online platforms. Some higher education institutions have successfully established or used appropriate online platforms such as online forums, web applications, or mobile applications to engage their community in ideation or crowdsourcing as a part of the value co-creation process. On the other hand, some HEIs have failed to engage their community in value co-creation activities, and even if they managed to engage some individuals in value co-creation once, they failed to sustain these individuals' engagement in value co-creation using online platforms. Using the Stimulus Organism Response (S-O-R) framework, this study examined the relationship between relevant personal factors (commitment and knowledge self-efficacy) and other perceived benefit motivational factors with value co-creation engagement. Data were collected from 308 respondents at five research universities in Malaysia. The Smart PLS software analysis tool was used for data analysis and validation. The results showed that personal factors and perceived benefits as a motivational factor had a significant effect on individual engagement in value co-creation. However, the significance of these findings varies from one individual to another. The implications of these findings are discussed.